Upper-class employers, domestic workers and pandemic - Kogan, Liuba (2023)
This article analyzes the decisions about paid and unpaid domestic work made by upper- and professional-class women from Lima (married with children of legal age) who stopped employing domestic workers during the lockdown imposed in response to the Covid-19 pandemic. The research highlights a world of winners and losers: of employers who undertake housework with the help of family members, lower their cleaning standards, use latest-generation domestic appliances, or procure third-party services; and of domestic workers who are laid off, experience pay reductions, or stop receiving the corresponding benefits.